2018
DOI: 10.3989/mc.2018.14016
|View full text |Cite
|
Sign up to set email alerts
|

Porous alkali activated materials with slow alkali release dynamic. Role of composition

Abstract: Alkali activated materials (AAM) based on calcined metakaolin or illite clay together with waste by-products, such as waste glass or aluminium scrap recycling waste, were tested as value-added materials for pH stabilization in biogas technology where decrease of pH should be avoided. Porous materials with ability to slowly leach alkalis in the water media thus providing continuous control of the pH level were obtained. XRD, FTIR, SEM and titration methods were used to characterize AAM and their leaching proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…After the 28 th day, the pH decay was 2.4 and 2.6, respectively, for compositions 50RM_0.30 and 50RM_0.40. The pH fluctuation over time of the RM-based spheres is narrower than that reported for metakaolin-waste inorganic polymers (~ 4-5 [25] and ~ 3-4 [19]), and metakaolin-based geopolymer spheres (3.7 [16]), which demonstrates the potential of the RM-based spheres as pH regulators. Other studies have reported lower pH decay over time: 1.6-1.9…”
Section: A C C E P T E Dmentioning
confidence: 63%
“…After the 28 th day, the pH decay was 2.4 and 2.6, respectively, for compositions 50RM_0.30 and 50RM_0.40. The pH fluctuation over time of the RM-based spheres is narrower than that reported for metakaolin-waste inorganic polymers (~ 4-5 [25] and ~ 3-4 [19]), and metakaolin-based geopolymer spheres (3.7 [16]), which demonstrates the potential of the RM-based spheres as pH regulators. Other studies have reported lower pH decay over time: 1.6-1.9…”
Section: A C C E P T E Dmentioning
confidence: 63%
“…The leaching of alkalis is affected by three main factors: Chemical composition of raw materials (type of precursor and activator, alkali activator solution/solid ratio), physical properties (porosity, pore structure), and production method of AAM (curing conditions, thermal treatment, etc.) [2,5,[11][12][13]. The previous results from different studies have shown that calcined illite clay [3], biomass-fly ash [5], natural zeolite [14], glass waste and slag blend [15], and metakaolin [2,16] can be used as raw materials for production of AAM.…”
Section: Introductionmentioning
confidence: 99%